A two-stage extraction procedure for insensitive munition (IM) explosive compounds in soils. (December 2016) - Felt, Deborah; Gurtowski, Luke; Nestler, Catherine C.; Johnson, Jared; Larson, Steven
Abstract: The Department of Defense (DoD) is developing a new category of insensitive munitions (IMs) that are more resistant to detonation or promulgation from external stimuli than traditional munition formulations. The new explosive constituent compounds are 2, 4-dinitroanisole (DNAN), nitroguanidine (NQ), and nitrotriazolone (NTO). The production and use of IM formulations may result in interaction of IM component compounds with soil. The chemical properties of these IM compounds present unique challenges for extraction from environmental matrices such as soil. A two-stage extraction procedure was developed and tested using several soil types amended with known concentrations of IM compounds. This procedure incorporates both an acidified phase and an organic phase to account for the chemical properties of the IM compounds. The method detection limits (MDLs) for all IM compounds in all soil types were <5 mg/kg and met non-regulatory risk-based Regional Screening Level (RSL) criteria for soil proposed by the U.S. Army Public Health Center. At defined environmentally relevant concentrations, the average recovery of each IM compound in each soil type was consistent and greater than 85%. The two-stage extraction method decreased the influence of soil composition on IM compound recovery. UV analysis of NTO established an isosbestic point based on varied pH at a detection wavelength of 341 nm. The two-stage soil extraction method is equally effective for traditional munition compounds, a potentially important point when examining soils exposed to both traditional and insensitive munitions. Highlights: A two-stage soil extraction method was developed with high recovery of IM munitions. Extraction evaluated with soil types from areas where IM are produced/deployed. The Method Detection Limits (MDLs) were <5 mg/kg. MDLs met non-regulatory criteria proposed by U.S. Army Public Health Center. Two-stage extraction effective for soils contaminated with IM/traditional munitions.